2020
DOI: 10.1590/0102-311x00119119
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy with negative physical oral health impact on quality of life in older adults

Abstract: Abstract: Oral impairments can affect overall health and life expectancy in older adults. Our study evaluates the life expectancy with negative physical oral health impact on quality of life (POHIQoL) among older adults. Life expectancy with negative POHIQoL was estimated by the Sullivan method, using the prevalence of POHIQoL - obtained in the Health, Well-being and Ageing (SABE Study); and official mortality data for adults aged 60 years or older living in São Paulo, Brazil. Between 2000 and 2010, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 34 publications
0
4
0
11
Order By: Relevance
“…Al aplicar la estrategia de búsqueda se identificaron en las bases bibliográficas electrónicas Medline, 2810 registros, en LILACS registros, en SciELO, 58 registros y en EBSCO Dentistry & Oral Sciences, 162 registros, totalizando 3134 artículos, los que fueron sometidos al protocolo PRISMA y de dicha aplicación se obtuvieron 17 artículos (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) (Figura 1).…”
Section: Resultsunclassified
“…Al aplicar la estrategia de búsqueda se identificaron en las bases bibliográficas electrónicas Medline, 2810 registros, en LILACS registros, en SciELO, 58 registros y en EBSCO Dentistry & Oral Sciences, 162 registros, totalizando 3134 artículos, los que fueron sometidos al protocolo PRISMA y de dicha aplicación se obtuvieron 17 artículos (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) (Figura 1).…”
Section: Resultsunclassified
“…Despite the increase in EFLE for most groups from 2006 to 2016, sex and education inequalities remained significant in the studied period. Inequalities in healthy life expectancy were suggested in studies using other general health [2][3][4][5][6][7] and oral health 23 measures, and might be explained by the worse health and living conditions of the most vulnerable groups. 36,37 The pro-rich inequalities in tooth loss 38 and dental care may be explained by the higher use of dental services, especially for preventive reasons, among the higher educated.…”
Section: Discussionmentioning
confidence: 99%
“…37 Consistent with previous studies, women expect to live longer but with more disabilities and diseases. [2][3][4][5][6][7]23 Higher male mortality at early ages, in addition to contributing to a decrease in TLE, could allow the composition of a more homogeneous and healthier group of older men due to a selection mechanism. 2,7 Furthermore, tooth loss seems to be more prevalent 10,32 and to occur at an early age among women, 32 which in part can be explained by financial, social and health conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on the association between undernutrition and oral hygiene [23][24][25]. Furthermore, studies also assert that oral care (including oral healthcare) is effective at preventing undernutrition and aspiration pneumonia as well as extending patients' life expectancy [24][25][26][27]. The effectiveness of oral care in preventing pneumonia is attributable to reducing oral bacteria and inducing swallowing reflexes [14,15]; however, no other reports support this finding.…”
Section: Discussionmentioning
confidence: 99%